2018
DOI: 10.7567/jjap.57.08pf02
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanostructures electrodeposited on graphene oxide-modified indium tin oxide glass as a surface-enhanced Raman scattering-active substrate for ultrasensitive detection of dopamine neurotransmitter

Abstract: Dopamine (DA) is a neurotransmitter closely relate to the dysfunction and the deficiency of the dopaminergic system. Surface-enhanced Raman scattering (SERS) is a promising analytical tool that can identify the DA levels in biological fluid containing various components. In this study, we fabricated a SERS-active substrate by electrodepositing Au nanoparticles (NPs) on the indium tin oxide (ITO) glass modified with graphene oxide. The morphology of the Au NPs was optimized by adjusting the concentration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…45 The XRD pattern of ITO/Au NPs film displays extra peaks at (111), which is related to the fcc crystal structure of Au placed on the ITO glass. 46 The ITO/Ag and ITO/APTES/Ag showed almost identical XRD peaks to those of the ITO/Au. This is because Ag NPs also have a characteristic peak at the (111) lattice surface, corresponding to a 2θ angle of 38.2°.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…45 The XRD pattern of ITO/Au NPs film displays extra peaks at (111), which is related to the fcc crystal structure of Au placed on the ITO glass. 46 The ITO/Ag and ITO/APTES/Ag showed almost identical XRD peaks to those of the ITO/Au. This is because Ag NPs also have a characteristic peak at the (111) lattice surface, corresponding to a 2θ angle of 38.2°.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…All four XRD patterns of the four substrates show the characteristic diffraction peaks of the ITO at 21.5°, 30.5°, 35.4°, 45.5°, 50.9°, and 60.6° with lattice faces (221), (222), (400), (431), (440), and (622), respectively, the network surface (222) being the most developed, corresponding to the crystal structure of indium tin oxide (ITO) . The XRD pattern of ITO/Au NPs film displays extra peaks at (111), which is related to the fcc crystal structure of Au placed on the ITO glass . The ITO/Ag and ITO/APTES/Ag showed almost identical XRD peaks to those of the ITO/Au.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the SERS enhancement effect of the AuNPs@PP-SH devices for the detection of PC in aqueous fluids, we prepared a quaternary mixture containing PC (1 mM), DA (1 mM), UA (1 mM), and AA (1 mM) in PBS buffer solution and tested it on the chips using SERS spectroscopy with comparison to the mixture solutions of [HA (1 mM) + DA (1mM) + UA (1 mM) + AA (1 mM)] and [IS (1 mM) + DA (1mM) + UA (1 mM) + AA (1 mM)] (Figure 9). Previous reports have shown that the strongest peak at 1331, 1386, and 1567 cm −1 can be chosen to estimate the correlation between the Raman intensity and the concentration of DA, AA, and UA, respectively (Pucetaite et al, 2016; Cholula-Díaz et al, 2018; Phung et al, 2018). The AuNPs@PP-SH devices provided a higher-intensity Raman signal for PC, due to its greater SERS activity (SERS hot spots), in the presence of DA, UA, and AA than did the PP-SH devices; nevertheless, discrimination of the overlapping region of signals from the DA, AA, and UA analytes from the background signals of AuNPs@PP-SH devices remained a major challenge in the fingerprint region (1300–1600 cm −1 ) (Figure 9h).…”
Section: Resultsmentioning
confidence: 99%
“…By optimizing the shape, size, and arm angle of a multi-branch nanoparticle, a highly efficient surface-enhanced Raman scattering (SERS) bio-sensor can be constructed at a desired resonant wavelength with polarizationindependent properties. Using these nanoparticles to enhance the SERS signal 30) for bio-sensor applications also can be envisioned. 31) Poynting flux in the scatter-field and total-field region respectively.…”
Section: Introductionmentioning
confidence: 99%